Nevus sebaceus of Jadassohn - high frequency ultrasound imaging and videodermoscopy examination. Case presentation - Bezugly, Artur; Sedova, Tatiana; Belkov, Pavel; Enikeev, Damir; Voloshin, Ruslan (Medicine and Pharmacy Reports, 2020)
Nevus sebaceus of Jadassohn (NSJ) is a congenital cutaneous hamartoma mainly developing from pilosebaceous unit cells. NSJ has the potential to develop into a variety of benign and malignant tumors, which are not limited to sebaceous differentiation. The dynamical monitoring for the earliest malignant transformation is necessary. Herein, we report the combined noninvasive NSJ examination with videodermoscopy in polarized and non-polarized light and high-frequency ultrasound (HFUS) imaging at 33 and 50 MHz. Typical NSJ dermoscopic signs where described, the internal nevus structure and its location, depths, and margins with surrounded tissues were examined with high-frequency ultrasound. Some HFUS characteristics for NSJ were described. Videodermoscopy and high-frequency ultrasound combined examination could be useful for NSJ dynamical monitoring in order to detect malignant transformation and to define necessary and sufficient tissue excision volume in case of surgical treatment.